Kedudukan Pengungsi Taliban di Indonesia Ditinjau dari Asas Non-Refoulement - M. Andhika Fikri Brilianto; Anwar Hanifuddin Fikri; Ika Kurnia Hardianty (Jurnal USM Law Review)
The purpose of this study is to describe the principle of Non-Refoulement, whether the application of the principle of Non-Refoulement is absolute or not, how urgent it is for Indonesia to apply the principle of Non-Refoulement, and how the position of Afghan refugees in Indonesia when viewed from the principle of Non-Refoulement and whether there are any sanctions obtained by Indonesia if it expels Afghan refugees from its territory. What is interesting to study is how the position of the Taliban refugees in Indonesia is viewed from the principle of Non-Refoulement, because the existence of these refugees is part of the law and the international community which indirectly involves Indonesia. The novelty of this research lies in the object studied, namely Afghan refugees and the principle of Non-Refoulement without involving other interdisciplinary legal aspects. The research method used is deductive qualitative. The results showed that the Non-Refoulement principle is a prohibition principle for expulsion of refugees, the application of the Non-Refoulement principle is not absolute based on article 33 paragraph 2 of the 1951 Convention, and Indonesia has no urgency to apply the Non-Refoulement principle. Furthermore, the position of Afghan refugees in Indonesia is as a transiting refugee and has rights in accordance with the 10 points of refugee position listed in the 1951 Convention, and no sanctions are applied if Indonesia does not accept the arrival of refugees to its country.